Educators' Strategies in Developing Students' Character at SMA IT Al Hijrah 2 Deli Serdang - Icha Nastasya Aulia, Salsabila Yasmin, Malik Ubaidillah, Ryan Fazli Zulna, Tengku Darmansah (Education Achievement: Journal of Science and Research, 2023)
This research aims to determine teacher strategies in forming environmentally caring character for students at SMA IT Al Hijrah Deli Serdang. This research is qualitative research with a descriptive approach. Data collection uses observation, interview and documentation techniques. The data source was obtained from the teacher. Data analysis techniques use data reduction, data presentation, and observation verification, increasing persistence and triangulation. The following are some of the findings from this research: (1) Teachers inSMA IT Al Hijrah Deli Serdang has used a very good strategy in building character for students. The teacher strategies in question include: consistency, routine activities, spontaneous activities, reprimands, integration into programmed activities, and transformation of school culture with habituation through extracurricular activities. (2) Teachers at SMA IT Al Hijrah Deli Serdang are faced with the challenges of globalization and need to be role models by getting used to midday and dhuha prayers to train students' discipline. The habit of reading the Koran is also integrated into learning activities to achieve the goal of character education with good morals. (3) Collaboration with the community is carried out in various activities, with the school and teachers involved in developing each activity. Regular meetings, both formal and informal, are held at least twice to communicate the school's vision, build a sense of mutual need, and gather community support.